The Role of Perceived Organizational Support in Reducing Job Cynicism: The Role of Perceived Organizational Support in Reducing Job Cynicism - سردار احمد بروا; دلاور توفيق نوا (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The current study examines the nature of the relationship and impact between perceived organizational support and organizational cynicism through the opinions of a sample of employees at Koya University in the Kurdistan Region of Iraq. The study problem was formulated by posing a number of questions, including: What is the level of perceived organizational support among employees at Koya University? What is the level of impact of perceived organizational support in reducing organizational cynicism among employees at Koya University? What is the level of organizational cynicism among employees at Koya University? The study mainly aims to determine the relationship and impact between perceived organizational support and organizational cynicism at Koya University. To achieve the study objectives, the researchers relied on the descriptive analytical approach. The study population includes (482) individuals and the study sample includes (150) individuals at Koya University. The comprehensive survey method was used by distributing the questionnaire to a community. The importance of the study lies in the importance of organizational cynicism, given its association with negative outcomes such as apathy, job resignation, despair, lack of trust, and doubt, among other negatives, leading to poor performance and conflicts between individuals and between individuals and the organization. SPSS v22 was used for data entry and processing. The study reached several conclusions, including that all sample members agreed, at moderate levels, that the organization under study, in which they work, possesses the requirements for implementing participatory decision-making. The study proposes employee participation and consultation when making decisions.